Impact of anthropogenic Pollution on Bujumbura Rivers: Toward Rivers and Lake Tanganyika Biodiversity Conservation, Burundi - C. Sibomana; S. Buhungu; D. Ntakirutimana; D. Nahimana (Journal of Applied Sciences and Environmental Management, 2024)
Despite its importance, Lake Tanganyika is threatened by pollution especially around Bujumbura, the largest city on its shores, leading to its biodiversity loss, habitat destruction and trophic system disturbance. Hence, the objective of this paper is to assess the impact of the anthropogenic pollution of Bujumbura on rivers using water quality physicochemical and macroinvertebrates community parameters. Four rivers were sampled and two stations, upstream and downstream the city were considered. EC, TDS, NH4, NO2- and BOD5 show high values downstream at all rivers on one hand and NO3- except for Kanyosha on the other hand, while DO values significantly decreased downstream the rivers except for Kanyosha too. This indicates the increasing water pollution from upstream to downstream, what is consistent with the dominance of the pollution-tolerant Chironomidae and Lumbriculidae dowmnstream and high density of the pollution-sensitive taxa from the EPT orders upstream the rivers. The same trend was observed with the reduction in macroinvertebrates diversity as Shannon diversity and Pielou evenness indices are lower downstream than upstream. The canonical correspondence analysis showed that the pollution-sensitive Hydropsychidae and Simuliidae and DO are associated with upstream stations while pollution-tolerant Chironomidae high densities on one hand and higher nutrients’ concentrations, TDS, EC and BOD5 on the other hand were associated with downstream stations.. This study indicates that rivers crossing Bujumbura have caused anthropogenic pollution thathas negatively affected rivers’ ecosystem causing biodiversity loss, community simplification and water quality alteration. More facilities should be installed for sufficient wastewater treatment before it is discharged into rivers and Lake Tanganyika.